Pembelajaran Menulis Teks Resensi di Kelas XI SMA Negeri 11 Pangkep - Anna Widi Astuti Djafar; Muhammad Saleh; Usman Usman (Indonesian Journal of Social and Educational Studies, 2021)
Learning To Write Review Text In Class XI SMA Negeri 11 Pangkep Universitas Negeri Makassar. This study aims to: describe the learning plan for writing review texts in class XI of SMA Negeri 11 Pangkep; Describe the implementation of learning to write review texts in class XI of SMA Negeri 11 Pangkep; Describes the assessment of learning to write review texts in class XI of SMA Negeri 11 Pangkep. The type of research used is qualitative research with a focus on three data in this study, namely (1) data on planning learning to write review texts, (2) data on the implementation process of learning to write review texts, and (3) data on assessment of learning to write review texts carried out. in class XI SMA Negeri 11 Pangkep. Data obtained through observation, documentation, and interviews. the results of the study show (1) the lesson plan made by the teacher contains all components of the nine aspects except for including the answer key to the question in the lesson plan, (2) the implementation of learning to write reviews in class XI SMA Negeri 11 Pangkep is not fully implemented in accordance with the planned implementation plan. made because learning takes place online during the covid-19 pandemic, (3) The learning assessment carried out by class XI teachers of SMA Negeri 11 Pangkep in reviewing text learning is cognitive and psychomotor assessment, while affective assessment comes from student portfolios during offline learning. Keywords: planning, implementation, and assessment